HUBUNGAN PENERAPAN KESEHATAN DAN KESELAMATAN KERJA (K3) DENGAN HASIL BELAJAR PRAKTIK TEKNIK PEMESINAN BUBUT SISWA JURUSAN TEKNIK PEMESINAN DI SMK NEGERI 1 PADANG - Ikhsanul Fikri; Irzal Irzal; Eko Indrawan; Jasman Jasman (Unversitas Negeri Padang, 2024)
Theì causeì of work accideìnts is baseìd on a lack of undeìrstanding in impleìmeìnting Occupational Safeìty and Heìalth (K3), as weìll as Occupational Safeìty and Heìalth (K3) reìgulations that areì not followeìd, theìreìforeì theì leìveìl of risk of accideìnts will beì veìry largeì. Theì purposeì of this study is to deìteìrmineì theì reìlationship beìtweìeìn occupational heìalth and safeìty (K3) and theì leìarning outcomeìs of meìchanical practiceì of gradeì XI studeìnts majoring in Meìchanical Eìngineìeìring at SMK Neìgeìri 1 Padang. Theì data colleìction teìchniqueì in this study useìs a queìstionnaireì with a likeìr scaleì. Theì data analysis teìchniqueì useìs SPSS softwareì with correìlation analysis that looks for variableì reìlationships. As a reìsult of theì data deìscription, a positiveì and significant reìlationship beìtweìeìn theì reìlationship beìtweìeìn theì impleìmeìntation of K3 and theì leìarning outcomeìs of Prakeìrin studeìnts in gradeì XI of Machining Eìngineìeìring SMK Neìgeìri 1 Padang was 0.490. at a significanceì leìveìl of 0.05 That this can proveì a positiveì influeìnceì beìtweìeìn theì two variableìs. Meìanwhileì, theì deìteìrminant valueì (R2) is 0.185. This meìans that theì reìlationship beìtweìeìn theì application of K3 and theì leìarning outcomeìs of latheì practiceì has a weìak cateìgory. From this, it can beì concludeìd that many factors affeìct theì impleìmeìntation of studeìnt K3, of which oneì of theìseì many things is studeìnt leìarning outcomeìs.